2023
DOI: 10.1111/psyp.14438
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐band oscillations and emotion: A review of studies on picture perception

Maurizio Codispoti,
Andrea De Cesarei,
Vera Ferrari

Abstract: Although alpha‐band activity has long been a focus of psychophysiological research, its modulation by emotional value during picture perception has only recently been studied systematically. Here, we review these studies and report that the most consistent alpha oscillatory pattern indexing emotional processing is an enhanced desynchronization (ERD) over posterior sensors when viewing emotional compared with neutral pictures. This enhanced alpha ERD is not specific to unpleasant picture content, as previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 226 publications
0
5
0
Order By: Relevance
“…This suggested that under the HPB condition, some relevant regions of the brain were activated compared to the CC. A recent review of Alpha-band oscillations and emotion pointed out that the emotional modulation of alpha ERD (enhanced desynchronization) reflected the engagement of the motivational systems when a significant stimulus is detected ( Codispoti et al, 2023 ). Accordingly, in our research, the high perceived benefits in the decision-making process acted as a significant stimulus, triggering the individual’s motivation to pursue benefits and emotions related to benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that under the HPB condition, some relevant regions of the brain were activated compared to the CC. A recent review of Alpha-band oscillations and emotion pointed out that the emotional modulation of alpha ERD (enhanced desynchronization) reflected the engagement of the motivational systems when a significant stimulus is detected ( Codispoti et al, 2023 ). Accordingly, in our research, the high perceived benefits in the decision-making process acted as a significant stimulus, triggering the individual’s motivation to pursue benefits and emotions related to benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The function further filters the EEG data to frequencies between 0.5 Hz around the ssVEP target frequency of 7.5 Hz. This has the added benefit of limiting the possible influence of the alpha oscillation which ranges from 8 to 12 Hz, which are known to be modulated by emotional perception (Codispoti et al, 2023;Sarlo et al, 2005). A Hilbert transformation is then applied to derive the instantaneous amplitude at this frequency over time.…”
Section: Eeg Preprocessingmentioning
confidence: 99%
“…According to several studies, the viewing of emotional pictures activate corticolimbic motivational systems (appetitive and aversive) that, in turn, enhance attention allocation to efficiently process the stimulus itself (Öhman, 1992;Hamm et al, 2003;Bradley, 2009;Gottlieb, 2012;Codispoti et al, 2016;Mulckhuyse, 2018). In terms of electrocortical activity, it is well established that emotional pictures (pleasant and unpleasant) elicit a larger late positive potential (LPP) and Alpha event-related desynchronization (Alpha ERD) than neutral images (Schupp et al, 2006;De Cesarei and Codispoti, 2011;Ferrari et al, 2020;Schubring and Schupp, 2021;Ferrari et al, 2022), and these cortical modulatory effects have been interpreted as reflecting both the engagement of attentional resources by emotional stimuli and the activation of motivational systems (Schupp et al, 2006;Lang et al, 2008;Ferrari et al, 2011;Weinberg and Hajcak, 2011; for a review focusing on similarities and differences between these measures see Codispoti et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that Alpha-ERD emotional modulation is unaffected by top-down factors, such as task-related processes ( Schubring and Schupp, 2019 ; Codispoti et al, 2023 ), or picture repetition ( Ferrari et al, 2015 ; 2020 ; 2022 ; Schubring and Schupp, 2021 ). The affective modulation of the LPP is affected by stimulus repetition ( Codispoti et al, 2007 ; Mastria et al, 2017 ), and there is evidence of stronger habituation when pictures are outside the attentional focus, and behave as distractors ( Ferrari et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%